2004
DOI: 10.4141/s03-031
|View full text |Cite
|
Sign up to set email alerts
|

Properties of soils influenced by ectomycorrhizal fungi in hybrid spruce [Picea glauca × engelmannii (Moench.) Voss]

Abstract: [91][92][93][94][95][96][97][98][99][100][101][102]. Soil properties of rhizosphere zones in coniferous forests are influenced by the presence of ectomycorrhizae. To elucidate the role of ectomycorrhizae (ECM) on the alteration of chemical and mineralogical properties of soils, soil pH, total C and N, cation exchange capacity, and the contents of mica, chlorite, and kaolinite, 2:1 type expandable clays, and amorphous minerals were compared in two soils, soils influenced by ectomycorrhizal fungi (ECS) and non-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
1
6
0
1
Order By: Relevance
“…Except for the LFH horizon samples, the higher CEC in R compared with NR soils are consistent with other studies on the same or other tree species (Arocena et al 1999;Glowa et al 2004;Turpault et al 2007). The high CEC in R soils may be attributed to the presence of clay minerals and/or organic matter.…”
Section: Chemical and Mineralogical Properties Of Rhizosphere And Nonsupporting
confidence: 91%
See 2 more Smart Citations
“…Except for the LFH horizon samples, the higher CEC in R compared with NR soils are consistent with other studies on the same or other tree species (Arocena et al 1999;Glowa et al 2004;Turpault et al 2007). The high CEC in R soils may be attributed to the presence of clay minerals and/or organic matter.…”
Section: Chemical and Mineralogical Properties Of Rhizosphere And Nonsupporting
confidence: 91%
“…These results were consistent with previous studies on the same tree species. Glowa et al (2004) reported a pH of 5.1 for nonectomycorrhizosphere (N-ECM) soil, which was significantly different from the pH of 4.1 and 4.3 for ectomycorrhizosphere (ECM) soils of P. glauca. Arocena et al (1999) reported a pH of 5.2 for N-ECM soil, which was not significantly different from the pH of 4.6 and 4.9 for ectomycorrhizosphere soils of A. lasiocarpa.…”
Section: Chemical and Mineralogical Properties Of Rhizosphere And Nonmentioning
confidence: 83%
See 1 more Smart Citation
“…These soluble elements (from mineral weathering and mass flow) can thus be fixed on the organic matter and on the mineral surfaces thus enriching the rhizosphere. Glowa et al (2004) even demonstrated in coniferous forests that properties of rhizosphere are strongly influenced by the presence of ectomycorrhizae. These authors observed that total C and N, CEC as well as exchangeable K + , and Na + were significantly higher in soils influenced by ectomycor- 3,0 3,0 rhizal fungi.…”
Section: Discussionmentioning
confidence: 95%
“…This acidification of the rhizosphere in the Norway spruce stands could also reveal differences in the activities among the microbial communities colonizing the Norway spruce roots and those colonizing the other species. For example, Glowa et al (2004) demonstrated in a spruce forest, that the colonization of roots by certain species of ectomycorrhizal fungi can significantly decrease the pH of the rhizosphere. As observed by Calvaruso et al (2009), the exudation of large amount of protons by Norway spruce roots and root-associated microorganisms generated an important loss of interlayer Al in the rhizosphere (clay-sized fraction), three times higher than that measured for the oak.…”
Section: Discussionmentioning
confidence: 98%